Determinants of Halal Cosmetics Purchase Intention on Indonesian Female Muslim Customer - Haro, Andrian (Journal of Entrepreneurship, Business and Economics; Vol 6 No 1 (2018), 2018)
The purpose of this research was to analyze partially the influence of attitude, subjective norm, perceived behavioral control, and knowledge towards customer purchase intention. Data were collected through a questionnaire of 200 respondents from Indonesian female Muslim customer. The research used a descriptive and explanatory methods which analyzed by using multiple regression analysis through SPSS software. The results showed there are partially positive and significant influence between attitude, subjective norm, and knowledge towards halal cosmetics purchase intention. Meanwhile, perceived behavioral control has no significant influence on customer purchase intention. These results will be a good recommendation for cosmetics manufacturers in producing and promoting their halal cosmetics product by considering the influence of consumers' attitude, subjective norm and knowledge. This research is expected to be useful for the development of halal cosmetics industry in the future.  Research paper Keywords: Theory of planned behavior, purchase intention, knowledge, halal cosmetics Reference to this paper should be made as follows: Haro, A. (2018). Determinants of Halal Cosmetics Purchase Intention on Indonesian Female Muslim Customer, Journal of Entrepreneurship, Business and Economics , 6 (1), 78–91.